2012
DOI: 10.1523/jneurosci.1947-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Musical Expertise Induces Audiovisual Integration of Abstract Congruency Rules

Abstract: Perception of everyday life events relies mostly on multisensory integration. Hence, studying the neural correlates of the integration of multiple senses constitutes an important tool in understanding perception within an ecologically valid framework. The present study used magnetoencephalography in human subjects to identify the neural correlates of an audiovisual incongruency response, which is not generated due to incongruency of the unisensory physical characteristics of the stimulation but from the violat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
79
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 44 publications
14
79
1
2
Order By: Relevance
“…The organization of this network indicates that musicians make greater use of the temporal sources (and auditory information accordingly). The present results closely relate to previous results reported by our group (9,10). This analysis further revealed that musicians showed significantly greater activity than nonmusicians in superior frontal, superior temporal, and lingual gyrus when confronted with incongruences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The organization of this network indicates that musicians make greater use of the temporal sources (and auditory information accordingly). The present results closely relate to previous results reported by our group (9,10). This analysis further revealed that musicians showed significantly greater activity than nonmusicians in superior frontal, superior temporal, and lingual gyrus when confronted with incongruences.…”
Section: Discussionsupporting
confidence: 92%
“…The behavioral results are in line with previously reported ones (9), indicating that musicians' prior experience in musical reading is associated with a behavioral benefit. Previous psychophysical studies have reported similar results among nonmusicians, indicating that the identification of cross-modal correspondences between pitch height and the height of a visual stimulus may be innate (13).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Music is capable of activate at the same time millions of neural networks and stimulate the most diverse brain areas. It's clear that this audio-visual and abstract integration will develop neurogenesis [69,70]. In 2013, people between 60 to 84 years old have been studied during 4 months of piano lessons and the results showed an improvement of attention, mood, cognitive skills, motor function, visual memory and executive functioning [71][72][73] suggested that 60-75 minutes of music training for a period of 5 to 6 weeks is good enough to help elderly to reverse age-related decline.…”
Section: New Experiences Meditation and Sleepmentioning
confidence: 99%